Defensa de la universidad pública y notas sobre la enseñanza del Derecho (Penal), la academia, el legislador, la jurisprudencia y la "ciencia" del Derecho Penal - Díaz y García Conlledo, Miguel (2024)
"Speech of thanks for the appointment as Honorary Professor of the University of Buenos Aires," delivered on October 28, 2024, at the UBA School of Law.